Spatial transcriptomics reveals Inhba/Smad2/E2f4 axis in Lrp2high thecal cell proliferation in androgen-induced PCOS mice - Luo, Man; Tian, Xiaona; Li, Li; Zhang, Guomei; Liu, Wenzhi; Mei, Linlin; Li, Haoran; You, Xiaoyan; Zhang, Dongmei; Zhou, Mengsi; Xiao, Cheng; Ye, Jianping; et al. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by elevated androgen levels and impaired follicular development. A hallmark of PCOS is the excessive proliferation of thecal cells (TCs), which are critical for androgen production. However, the molecular mechanisms underlying this aberrant cellular expansion remain incompletely understood.MethodsA DHEA-induced mouse model was used to recapitulate the hormonal and ovarian features of human PCOS. Spatial transcriptomics was employed to profile gene expression in ovarian tissue at cellular resolution. Differential expression analysis, pathway enrichment, and spatial co-localization were performed to identify regulatory networks. Functional assays were conducted in cultured TCs using siRNA-mediated knockdown of target genes, and cell proliferation and cell cycle progression were evaluated using EdU incorporation and flow cytometry.ResultsSpatial transcriptomic profiling revealed widespread transcriptional changes in the ovaries of PCOS mice, including a marked expansion of a TCs subpopulation with high Lrp2 expression. This subset exhibited enhanced activity in genes involved in androgen synthesis and cell cycle regulation. A signaling axis comprising Inhba, Smad2, and E2f4 was identified as a key regulator of this proliferative response, with all three genes co-expressed in the affected regions. Knockdown of any component of this axis significantly suppressed TCs proliferation in vitro, with the greatest effect observed upon Inhba silencing.ConclusionThe Inhba/Smad2/E2f4 axis contributes to thecal cell hyperplasia and androgen excess in PCOS, and may serve as a mechanistic entry point for further investigation into the regulation of TCs proliferation in this disorder.